Pendampingan Mahasantri melalui Diskusi Interaktif untuk Meningkatkan “High Order Thinking Skills” di PP. Sunan Drajat - Ahmad Zidan Danutirto; Muhammad Prasetyo Nugroho; M. Nur Qomaruddin A.; Abdul Hamid; Rachmad Ardy Kurniawan; M. Muhlis (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Assistance for students of the Sunan Drajat Islamic Boarding School in order to prepare cadres who have the ability or skill